2015
DOI: 10.1039/c4tc02315c
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular hierarchy among halogen and hydrogen bond donors in light-induced surface patterning

Abstract: Halogen bonding, a noncovalent interaction possessing several unique features compared to the more familiar hydrogen bonding, is emerging as a powerful tool in functional materials design. Herein, we unambiguously show that one of these characteristic features, namely high directionality, renders halogen bonding the interaction of choice when developing azobenzene-containing supramolecular polymers for light-induced surface patterning. The study is conducted by using an extensive library of azobenzene molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
115
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 88 publications
(118 citation statements)
references
References 79 publications
3
115
0
Order By: Relevance
“…14a, allows for tuning the halogen bonding interaction strength with pyridine. 144,145 As Fig. 14b and c show, there is a direct correlation with the halogen bond strength and SRG formation efficiency, the iodine-capped (resulting in relatively strong halogen bonding) azobenzene complexed with P4VP resulting in the highest and fluorinecapped (no specific interaction with P4VP) resulting in the lowest SRGs.…”
Section: 141mentioning
confidence: 95%
“…14a, allows for tuning the halogen bonding interaction strength with pyridine. 144,145 As Fig. 14b and c show, there is a direct correlation with the halogen bond strength and SRG formation efficiency, the iodine-capped (resulting in relatively strong halogen bonding) azobenzene complexed with P4VP resulting in the highest and fluorinecapped (no specific interaction with P4VP) resulting in the lowest SRGs.…”
Section: 141mentioning
confidence: 95%
“…Surprisingly, they reported that for their hydrogen bonded polymer (P4VP-OH(DMA)), only 1 mol % of chromophore loading was sufficient to obtain efficient gratings ( Figure 5a); hence, the inscription rate is lowered by decreasing chromophore concentration. In addition to the use of hydrogen bonds to create supramolecular azobenzene-containing polymers, Priimagi and co-workers reported on the creation of supramolecular polymers by use of halogen bonds [78][79][80][81]. They determined the superiority of halogen-bonded polymer-azobenzene complexes over the analogous hydrogen-bonded complexes.…”
Section: Light-induced Permanent Surface Relief Gratings In Linear Azmentioning
confidence: 99%
“…Recently, a more comparative study of different halogen bond donor chromophores showed that the efficiency of the SRG formation is increased with interaction strength (Figure 6). Moreover, the most effective halogen bond donor was found to be a iodoacetylene azo dye [81]. Seki et al reported on liquid crystalline linear polymer systems that can create SRGs with light [38,82,83].…”
Section: Light-induced Permanent Surface Relief Gratings In Linear Azmentioning
confidence: 99%
See 2 more Smart Citations